Termination of Employment Contract Based on Unsatisfactory Results of the Probationary Period - Karapetyan, Mane (Bulletin of Yerevan University C: Jurisprudence, 2025)
The article presents the institute of the probationary period and the peculiarities of terminating an employment contract with a person on probation, both from a substantive and procedural point of view. Reference is made to doctrinal approaches, the experience of foreign countries, and the relevant decision of the Court of Cassation. Proposals for legislative amendments are presented, which are aimed at clarifying and more fully regulating the institute of terminating an employment contract on the basis of a probationary period. In particular, it was proposed to clarify the possibility of testing the employee’s human and other qualities during the probationary period and, accordingly, the employer’s right not to indicate the exact reason for the termination of the contract in the dismissal order.